2000
DOI: 10.1614/0890-037x(2000)014[0480:iogwrh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Glyphosate with Residual Herbicides in No-Till Soybean (Glycine max) Production1

Abstract: Glyphosate is often mixed with residual herbicides to control emerged weeds in no-till crop production systems. Field studies were conducted in Ohio from 1992 to 1994 to evaluate the weed control provided by residual herbicides and reduced rates of glyphosate in full-season, no-till soybean. Herbicide treatments were applied at two timings to examine the effect of weed size. At 4 wk after treatment, greater than 85% Pennsylvania smartweed control was obtained with metribuzin plus chlorimuron and linuron plus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…Tank mixtures of glyphosate plus S-metolachlor in GR cotton increased control of broadleaf signalgrass (Urochloa platyphylla), goosegrass (Eleusine indica), large crabgrass (Digitaria sanguinalis), and yellow foxtail (Setaria pumila) by 14% to 43% compared to glyphosate alone (Clewis et al, 2006). In addition, Vanlieshout & Loux (2000) studied the interactions of glyphosate with residual herbicides in no-till soybean production and observed that the foliar activity of residual herbicides can improve the control of emerged weeds when associated with glyphosate. In Brazil, Procopio et al (2007) observed that the addition of imazethapyr and chlorimuron-ethyl to POST applications of glyphosate in GR soybean improved the control of Euphorbia heterophylla, Commelina benghalensis, Chamaesyce hirta, Leucas martinicensis and Ipomoea grandifolia compared to a single POST application of glyphosate alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tank mixtures of glyphosate plus S-metolachlor in GR cotton increased control of broadleaf signalgrass (Urochloa platyphylla), goosegrass (Eleusine indica), large crabgrass (Digitaria sanguinalis), and yellow foxtail (Setaria pumila) by 14% to 43% compared to glyphosate alone (Clewis et al, 2006). In addition, Vanlieshout & Loux (2000) studied the interactions of glyphosate with residual herbicides in no-till soybean production and observed that the foliar activity of residual herbicides can improve the control of emerged weeds when associated with glyphosate. In Brazil, Procopio et al (2007) observed that the addition of imazethapyr and chlorimuron-ethyl to POST applications of glyphosate in GR soybean improved the control of Euphorbia heterophylla, Commelina benghalensis, Chamaesyce hirta, Leucas martinicensis and Ipomoea grandifolia compared to a single POST application of glyphosate alone.…”
Section: Introductionmentioning
confidence: 99%
“…The PRE application of residual herbicides, such as sulfentrazone, may delay the establishment of GR weed biotypes (Krauz & Young, 2003). The addition of the PRE residual herbicide in the program can provide more consistent control of hard-to-control weeds, delay the post Residual herbicides in weed management for glyphosate-resistant ... planting application timing for glyphosate, and reduce selection pressure for resistant biotypes (Walsh & Powles, 2007). However, studies conducted by Nurse et al (2007) showed no advantage from the use of flufenacet plus metribuzin followed by glyphosate in comparison to a single application of glyphosate on Echinochloa crus-galli, Setaria viridis, Chenopodium album, Ambrosia artemisiifolia, and Abutilon theophrasti.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate efficacy is particularly influenced by weed size [22] [23]. In some biotypes of Conyza spp., glyphosate control fails due to an inappropriate dose when there is a delay in application that allows plants to reach sizes that are difficult to kill consistently [11].…”
Section: Introductionmentioning
confidence: 99%
“…En particular glifosato el tamaño de la maleza puede afectar la eficacia (Vanlieshout & Loux, 2000). A pesar de que el efecto de la especie y estado de desarrollo de la planta es conocido, la dosis de glifosato que permite el control no se conoce para las especies estudiadas en este trabajo.…”
Section: Introductionunclassified